Effect of planting densities on grain filling and kernel dehydration of maize (Zea mays) - Zhao, P u; wang, jin; juntawong, niran; aekatasanawan, chokechai; kermanee, prasart; roytrakul, sittiruk; xie, juliang; yue, haiwang; jia, yinsuo; a, chunhong m (The Indian Journal of Agricultural Sciences, 2020)
Maize (Zea mays L.) yield is greatly affected by the environmental and cultivate pattern. Grain filling and dehydration play important roles in maize grain dry mass accumulation and are important biological processes in maize growth and development. Four maize cultivars were planted at Hebei province with planting densities of 60000 and 75000 plants/ha during 2017-18. The kernel fresh weight and dry weight of four cultivars were measured at 15, 22, 29, 36, 43, 50 and 57 days after pollination of two planting densities. Logistic model was used to estimate the grain filling process in different environments. The results showed that the maximum filling rates of all cultivars under two planting densities were attained at about 25 days after pollination. The grain filling period was longer under the planting density of 60000 plants/ha. Meanwhile, the grain dehydration was slower. With the increased of planting density, 100-grain weight of per plant decreased while the yield increased. The higher yield was contributed by the larger numbers of plants. It indicated that suitable higher planting density will enhance the yield of maize. Bract, cob and grain water content were significantly correlated. This study indicated a negative effect of dense planting on grain filling.